2013
DOI: 10.1182/blood-2013-08-519413
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived CD19-targeted T cells cause regression of malignancy persisting after allogeneic hematopoietic stem cell transplantation

Abstract: Key Points Donor-derived anti-CD19-CAR T cells cause regressions of refractory malignancies after allogeneic transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
417
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 533 publications
(432 citation statements)
references
References 45 publications
10
417
3
2
Order By: Relevance
“…In patients, CAR-transduced T cells are able to clear large tumor burdens, sometimes leading to tumor lysis syndrome (8). We confirmed the high efficacy of the CAR-transduced T cells in cytotoxicity assays.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In patients, CAR-transduced T cells are able to clear large tumor burdens, sometimes leading to tumor lysis syndrome (8). We confirmed the high efficacy of the CAR-transduced T cells in cytotoxicity assays.…”
Section: Discussionsupporting
confidence: 64%
“…CARs activate T cells through intracellular signaling domains such as CD3z, which is improved by costimulation including CD28 or 4-1BB (6). Recently, transfer of such second generation CAR T cells targeting CD19 + B cell lymphoid leukemia has shown encouraging clinical results in treating patients with bulky tumors (7)(8)(9)(10). Although these results are galvanizing the field of adoptive cell therapy, clinical trials focusing on solid tumors have seen less success (11)(12)(13).…”
mentioning
confidence: 95%
“…This precautionary approach was required in the clinical trials of axi-cel, but we have not found this to be necessary in studies using CAR T cell constructs containing a 4-1BB co-stimulatory domain, including tisagenlecleucel, JCAR014, and JCAR017, in both ALL and NHL populations. Fever is typically the presenting symptom of CAR T cell-associated CRS (at least with 4-1BB CAR T cells), with critical illness arising 12-96 h later, if at all [7][8][9][10][11][12] . Patients can therefore be infused with CAR T cells in the outpatient setting and admitted to hospital at the time of fever development.…”
mentioning
confidence: 99%
“…We believe that this recommendation is not supported by clinical trial data from across the field of CAR T cell research to date, necessitating further studies to establish the comparative effectiveness of these agents. Tocilizumab is now approved by the FDA for the management of severe CRS based on extensive clinical data demonstrating the efficacy of this agent in the majority of patients 8,9,[11][12][13]15 . Siltuximab has not been studied as a first-line therapy for CRS and is not currently FDA-approved for this indication.…”
mentioning
confidence: 99%
“…Compared to donorlymphocyte infusions, which are infusions of resting T cells that can carry a significant risk of developing acute and/or chronic GVHD, 41 there have been no documented cases of acute or chronic GVHD following allogeneic CAR T cell therapy, including among those patients who received pre-infusion lymphodepletion. 4,10,21,42 CAR-T cell-mediated GVHD may be encountered more frequently with off-the-shelf allogeneic T cell products, whether they use viral-specific T cell populations and/or endogenous TCR knockdown 43 to dampen the risk of GVHD. Ideally, success with allogeneic CAR T cells would allow a broader, more cost-effective, and faster utilization of T cell-based therapies.…”
Section: Autonomous Signaling or Gvhdmentioning
confidence: 99%